Improvement of Mental Imagery after Prism Exposure in Neglect: A Case Study - Gilles Rode; Yves Rossetti; Ling Li; Dominique Boisson (Behavioural Neurology)
Previous work has shown that various symptoms of unilateral neglect, including the pathological shift of the subjective midline to the right, may be improved by a short adaptation period to a prismatic shift of the visual field to the right. We report here the improvement of imagined neglect after prism exposure in a patient with a left unilateral neglect. Despite a strong neglect observed for mental images as well as for conventional tests, the mental evocation of left-sided information from an internal image of the map of France map was fully recovered following prism adaptation to the right. This improvement could not be explained by the alteration of visuomotor responses induced by the prism adaptation. Prism adaptation may therefore act not only on sensory-motor levels but also on a higher cognitive level of mental space representation and/or exploration.